ANALISIS KOMPETENSI SUMBER DAYA MANUSIA DALAM MENANGGAPI KELUHAN PELANGGAN DI PDAM TIRTA KHAYANGAN KOTA SUNGAI PENUH: Bukhari Mualim - Mualim, Bukhari (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
Competence of Human Resources at the PDAM Tirta Khayangan office, Sungai Penuh city. Responding to customer complaints has not been fully implemented in accordance with the duties and functions of employees due to limited funds and the number of personnel they have. PDAM Tirta Khyangan Sungai Penuh is required to continue to improve the competence of human resources in responding to customer complaints as well as the approaches that should be developed to address increasing challenges faced in the field. In Kota Sungai Penuh a qualitative approach where data is obtained through interviews, from the results of the study it is known that many customers complain about recording meters, dirty water and many others. From the analysis applied, it can be concluded that the customers of PDAM Tirta Khayangan Sungai Penuh are expected to provide fast, precise and efficient service and overcome the obstacles that exist in customer complaints.